Free Will, Determinism, and Epiphenomenalism - Balaguer, Mark (Frontiers in Psychology, 2019)
This paper provides articulates a non-epiphenomenal, libertarian kind of free will—a kind of free will that’s incompatible with both determinism and epiphenomenalism—and responds to scientific arguments against the existence of this sort of freedom. In other words, the paper argues that we don’t have any good empirical scientific reason to believe that human beings don’t possess a non-epiphenomenal, libertarian sort of free will.